Conservation Agriculture - Farooq, Muhammad; Siddique, Kadambot H. M. (Springer International Publishing : Imprint: Springer, 2015)
Conservation agriculture-consisting of four components including permanent soil cover, minimum soil disturbance, diversified crop rotations and integrated weed management-is considered the principal pathway to sustainable agriculture and the conservation of natural resources and the environment. In this book leading researchers in the field describe the basic principles of conservation agriculture, and synthesize recent advances and developments in conservation agriculture research. This book is a ready reference on conservation agriculture and reinforces the understanding for its utilization to develop environmentally sustainable and profitable food production systems. The book describes various elements of conservation agriculture; highlights the associated breeding and modeling efforts; analyses the experiences and challenges in conservation agriculture in different regions of the world; and proposes some pragmatic options and new areas of research in this very important area of agriculture. This book is an invaluable source of information for scientists, teachers and students in the fields of agronomy, farming systems, ecology and environmental sciences.